ANTIBIOGRAM AND DRUG RESISTANCE PATTERN OF ESCHERICHIA COLI ISOLATED FROM DIARRHOEIC CALVES - Udaykar, Aniruddha; Sharda, Rakesh (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
Sixty two strains of E. coli isolated from 116 diarrhoeic faecal samples of calves were subjected to in vitro antibiogram studies towards nine antimicrobial drugs by disc diffusion method. Highest sensitivity was attributed to chloramphenicol (80.64%), followed by azithromycin (77.41%), tobramycin (46.77%), amoxycillin (35.48%), Co-trimeoxozole (35.48%), enrofloxacin (22.58%), cephalothin(12.90%), chlortetracycline (12.90%), and spectinomycin (8.06%) .Multiple drug resistance was observed in all the isolates exhibiting simultaneous resistance to 3 to 8 antibacterial agents. Forty two different antibiotic resistance patterns were recorded.